MINIMIZING RADICAL INTERPRETATIONS THROUGH THE STRENGTHENING OF RELIGIOUS MODERATION BASED ON THE BOOK OF HUJJAH AHLUSSUNAH WA AL JAMA’AH - Ula, Miftahul; Isbah, Faliqul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The book Hujjah Ahlussunah Wal Jama’ah by K.H. Ali Maksum Krapyak has gained widespread recognition as a primary reference in affirming the worship practices of the Nahdlatul Ulama group. Although this book is often used to support arguments against bid’ah practices, it actually contains texts that teach moderate values. The GP. Ansor organization, as an autonomous body of Nahdlatul Ulama focused on campaigns for unity, religious tolerance, and appreciation of differences, needs to understand that the studied book not only explains the literal meaning of texts but also conveys specific messages. This article aims to identify moderate religious texts in the book Hujjah Ahlussunah Wal Jama’ah, examine the implementation of teaching from the book, and reflect on the outcomes of this instruction. The community service method employs the Service Learning approach, establishing a connection between the academic community and academic tasks, with the goal of serving the community while developing academic and social skills through practical tasks in society. Through the service learning strategy, academics have the opportunity to develop life skills by imparting values acquired through the taught material to the community. The research results indicate that moderate religious texts in the book Hujjah Ahlussunah Wal Jama’ah are found in eight chapters, such as: Sending the Reward of Recitation, Charity and Righteous Deeds for the Deceased, Sunnah Prayers before Jumu'ah, Talqin for the Deceased, Tarawih Prayer, Determining the Beginning of Ramadan, Visiting Graves, the Punishment of the Grave, and Visiting the Prophet's Tomb. The teaching process of the book occurs in three stages: pre-implementation, implementation, and post-implementation. Reflection on the program's results encompasses four main points: the importance of religious moderation, the crucial role of Kiai in moderation, the significance of studying the book Hujjah Ahlussunah Wal Jama'ah, and the vital role of GP. Ansor.